The Political Economy of School Choice - Witte, John F.; Shober, Arnold F.; Schlomer, Paul A.; Engle, Par Jason (My University, 2004)
This analysis of the complex political economy of school choice, primarily as it has developed in Wisconsin, focuses on how various forms of choicemagnet and private contract schools, open enrollment, vouchers and charter schoolsinteract and compete with each other.